2017
DOI: 10.1016/j.jbusres.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

How do you feel today? Managing patient emotions during health care experiences to enhance well-being

Abstract: a b s t r a c t a r t i c l e i n f oHealth care customers (patients) experience heightened emotions due to high stakes from risks to life, health, and well-being. Understanding and managing emotions during service experiences is an important area of inquiry because emotions influence customer perceptions, future intentions and behaviors. Yet despite its significance, research focusing on the impact of emotions on customer experiences remains fragmented, lacking a theoretically based conceptual framework. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 52 publications
3
75
0
2
Order By: Relevance
“…However, Stalker (2008) and Orsega-Smith et al (2007) cautioned that the characteristics of social engagement among the elderly had to be carefully understood so that patterns of social behavior and network characteristics that improved well-being later in life could be analyzed. Similarly, McColl-Kennedy et al (2017) found that in the health care sector, understanding and managing patients' emotions during their interactions with other patients could also affect the patients' satisfaction and well-being.…”
Section: Customer-to-customer Interaction and Social Well-beingmentioning
confidence: 98%
“…However, Stalker (2008) and Orsega-Smith et al (2007) cautioned that the characteristics of social engagement among the elderly had to be carefully understood so that patterns of social behavior and network characteristics that improved well-being later in life could be analyzed. Similarly, McColl-Kennedy et al (2017) found that in the health care sector, understanding and managing patients' emotions during their interactions with other patients could also affect the patients' satisfaction and well-being.…”
Section: Customer-to-customer Interaction and Social Well-beingmentioning
confidence: 98%
“…How do customers manage multiple roles and identities, and how do customers prepare, encounter, and adjust role states in their daily life? (Lynch, 2007;McColl-Kennedy, Danaher, Gallan, Orshingher, Lervik-Olsen and Verma, 2017;McColl-Kennedy, Snyder, Elg, Witell, Helkkula, Hogan and Anderson, 2017;McColl-Kennedy et al, 2012). In fluid arrangements, who takes the role of the decision maker?…”
Section: Social Realmmentioning
confidence: 99%
“…To conceptualise the influence of customer participation on task-related affective well-being (TR-AWB) we draw support specifically from self-determination theory (SDT) (Ryan and Deci, 2000) and the framework offered by McColl-Kennedy et al (2017) on the elicitation of emotions on the service experience. According to Ryan and Deci (2000), SDT is a well thought out organismic theory of motivation and well-being.…”
Section: Customer Participation Well-being and Service Outcomesmentioning
confidence: 99%
“…In a more recent study, McColl-Kennedy et al (2017) have conceptualized the influence of events on emotional well-being of the customer in a healthcare service context. Their framework suggests that a 'trigger event' can lead to a dynamic series of subsequent emotional experiences, represented as sub-events comprising emotional relevance.…”
Section: Customer Participation Well-being and Service Outcomesmentioning
confidence: 99%